Indirect methods constraining nuclear capture - the Trojan Horse Method. (October 2020) - Tumino, A.; Spitaleri, C.; La Cognata, M.; Cherubini, S.; Guardo, G.L.; Gulino, M.; Indelicato, I.; Lamia, L.; Oliva, A.; Pizzone, R. G.; Prajapati, P.; Rapisarda, G.G.; et al.
Abstract: Reaction rates of nuclear processes of astrophysical relevance can be inferred using the Trojan Horse Method. This indirect technique is a valid alternative to direct measurements in particular when extremely low cross sections are involved. We will review its basic features in the framework of the theory of direct reactions and address the physics case of the 12 C+ 12 C fusion.